2015
DOI: 10.4049/jimmunol.1401587
|View full text |Cite
|
Sign up to set email alerts
|

mir-181a-1/b-1 Modulates Tolerance through Opposing Activities in Selection and Peripheral T Cell Function

Abstract: Understanding the consequences of tuning T cell receptor (TCR) signaling on selection, peripheral T cell function, and tolerance in the context of native TCR repertoires may provide insight into the physiological control of tolerance. Here we show that genetic ablation of a natural tuner of TCR signaling, mir-181a-1/b-1, in double-positive (DP) thymocytes dampened TCR and Erk signaling and increased the threshold of positive selection. Whereas mir-181a-1/b-1 deletion in mice resulted in an increase in the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 41 publications
4
50
0
Order By: Relevance
“…It is well established that modulation of expression of miR-181 affects TCR signaling strength, most prominently demonstrated at the level of Ca flux (8,10,11). Li et al (8) identified tyrosine phosphatases SHP-2 and PTPN-22 and ERK-specific phosphatases DUSP6 and DUSP5 as miR-181a targets in T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that modulation of expression of miR-181 affects TCR signaling strength, most prominently demonstrated at the level of Ca flux (8,10,11). Li et al (8) identified tyrosine phosphatases SHP-2 and PTPN-22 and ERK-specific phosphatases DUSP6 and DUSP5 as miR-181a targets in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-181a in adult human peripheral T cells resulted in increased Ca flux (9). Conversely, thymocytes from mice lacking miR-181a/b-1 displayed a defect in Ca signaling, whereas peripheral T cells from these only showed mild aberrations in baseline Ca flux (10,11). Accordingly, miR-181a has been shown to be involved in positive selection of double-positive thymocytes, regulation of central and peripheral tolerance, and production of invariant NK cells (10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of miR-181a expression reduced both downstream TCR signaling and positive and negative selection (Li et al 2007), leading to increased self-reactivity of mature T cells (Schaffert et al 2015). Another group reported that miR-181 is crucial for the development of iNKT cells in the thymus and that it works through controlling the phosphatase Pten, which in turn controls the metabolism of the cells (Henao-Mejia et al 2013).…”
Section: Inhibition Of Phosphatase Activity By Micrornasmentioning
confidence: 99%
“…The capacity of miR-181a to simultaneously target multiple serine/threonine and tyrosine phosphatases may make it the most attractive candidate in this category. This miRNA has been shown to enhance LCK and ERK activity by inhibiting DUSP5, DUSP6, PTPN11 (also known as SHP2), and PTPN22 [101] and to govern central and peripheral tolerance [102, 103]. Indeed, overexpression of miR-181a in T cells increased TCR sensitivity to cognate antigen and enhanced intracellular calcium flux upon TCR triggering, resulting in more pronounced release of IL-2 [101].…”
Section: Harnessing Mirna Biology To Enhance Adoptive T Cell Immunothmentioning
confidence: 99%